Antibacterial and Antifungal Effects of Ozonated Essential Oil of Sacha Inchi, Calcium Hydroxide, and the Combination of Both Against Enterococcus Faecalis and Candida Albicans: An In Vitro Study - Llaque-Bardales, María I. (2024)
The biggest challenge in root canal treatment is the elimination of microorganisms; therefore, new techniques are continually sought to achieve success. The agar diffusion method was used to determine the antibacterial and antifungal effect of ozonated Sacha Inchi essential oil, calcium hydroxide paste, and the combination of both. Brain heart infusion and sabouraud agar were the culture media for Enterococcus faecalis and Candida albicans respectively. The antibacterial and antifungal effects were determined using the inhibition halos that formed around the wells containing the drugs at 24 hours and 48 hours. From the study, the antibacterial and antifungal effects of the ozonized oil was greater after 6 hours, proportional to the higher concentration of peroxide. This study showed that the antibacterial effect of ozonated Sacha Inchi oil is superior to that of calcium hydroxide and the combination of both substances.